Figure of merit improvement of delafossite CuAlO2 with the addition of Fe and graphene - Daichakomphu, Noppanut; Harnwunggmoung, Adul; Chanlek, Narong; Sakdanuphab, Rachsak; Sakulkalavek, Aparporn (My University, 2019)
This study investigated the synthesis of delafossite CuAlO2 with Fe and graphene through a solid-state reaction method. The results of X-ray diffractometry showed that graphene was insoluble in delafossite CuAlO2 while Fe was substituted into Al sites, expanding the d-spacing. From X-ray photoelectron spectroscopy, graphene induced excess oxygen in the delafossite CuAlO2 structure via C–O–Cu bonds and improved the electrical conductivity. In addition, the thermal conductivity was reduced due to generation of point defects, phonon-phonon Umklapp and carrier-phonon scattering. The addition of Fe and graphene in CuAlO2 shows an improvement of ZT to 0.0114 at 573 K. This is attributable to its increase in charge carrier density, as well as a decrease in thermal conductivity. This study highlights the benefits of combining Fe and graphene in delafossite CuAlO2 as a prospective process for attaining a high figure of merit thermoelectric materials.
Keywords: CuAlO2; Fe doped; Graphene; Thermoelectric properties